Stability of canine and feline cerebrospinal fluid samples regarding total cell count and cell populations stored in “TransFix®/EDTA CSF sample storage tubes” - Meier, Laura (BMC Vet Res, 2020)
BACKGROUND: Because of fast leucocyte degeneration in cerebrospinal fluid (CSF) laboratory examinations of CSF samples should be performed approximately within 30 min after withdrawal. This study examines the storage of canine and feline CSF samples in “TransFix®/EDTA CSF Sample Storage Tubes” (Cytomark, Buckingham, UK) for preventing leucocytes from degeneration, so that routine and flow cytometry examinations are feasible up to 3 days after sampling. RESULTS: After storage in TransFix® tubes, leukocytes could not be adequately stained with Türk’s solution and differentiating between erythrocytes and leukocytes was cumbersome. In addition, the cell morphology could not be sufficiently assessed on cytospin preparations because of shrunken leukocytes and indistinct cell nuclei. In contrast, by flow cytometry, a significantly higher cell count was measured over the entire study period in the samples stored in TransFix® tubes compared to the untreated samples. The antibodies (AB) against CD3, CD4 and CD21, against CD11b and against CD45 showed a good binding strength and thus enabled a good differentiation of cell populations. However, after storage in the TransFix® tubes, monocytes were no longer detectable using an AB against CD14. CONCLUSION: Based on these results, “TransFix®/EDTA CSF Sample Storage Tubes” can be used for extended storage prior to flow cytometric analysis of lymphocytes and granulocytes in CSF samples but not for detecting monocytes. However, standard examinations, such as microscopic cell counting and morphological cell assessment should be performed on fresh CSF samples. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12917-020-02698-5.